Two types of deletion within integrated viral sequences mediate reversion of simian virus 40-transformed mouse cells. - Maruyama, K (1984)
Simian virus 40 (SV40) DNA insertions from SV40-transformed mouse cell line W-2K-11 and its revertants M18, M31, and M42 were cloned. W-2K-11 cells contain 1.5 copies of the SV40 sequences in a partially tandem duplicated form. The endpoints of the viral sequences at the virus-host junctions are located very close to those reported by others, indicating that there are some preferred sites for integration and rearrangement in SV40 sequences. One flanking cellular sequence is a long stretch of adenine and thymine with repeated AAAT, and the other is a stretch of guanine and cytosine with repeated CCG. There are patchy homologies between the flanking cellular sequences and the corresponding parental SV40 sequences. The sequences around both junctions were retained in all the revertants, whereas most of the internal SV40 sequences coding for large T antigen were deleted. The coding sequences for small T antigen are intact, and small T antigen was expressed in all the revertants. The fragments cloned from M18 and M42 were identical and 3.9 kilobases of SV40 sequences were deleted. The parental SV40 sequences around the deletion site have sequences capable of forming a secondary structure which might reduce the effective distance between the two regions. The SV40 DNA retained in M31 is colinear with SV40 virion DNA, and a unit length of SV40 DNA was deleted within the SV40 sequences present in W-2K-11 cells. These results indicated that two types of deletion occurred during the reversion, one between homologous sequences and the other between nonhomologous sequences.